Covid-19 Outcomes Among US Veterans - Jun-Chieh J. Tsay MD, MSc; Robert L. Smith MD (SAGE Publishing, 2022)
Comparing Covid-19 mortality among the U.S. population overall with mortality among Veterans Affairs patients and U.S. military patients.